Analisis Strategi Pemasaran Syariah Pada UMKM Fashion Muslim Nibras House Sooko Mojokerto di Era Digital - Nur Fadhilah Ahmadah; Mustofa Mustofa (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
Micro, small, and medium enterprises (MSMEs) play an important role in the Indonesian economy, both in creating jobs and strengthening the national economy. However, amid the rapid pace of digital technology development, MSMEs cannot rely solely on traditional methods such as manual or offline marketing. Indonesia is a country with a Muslim majority population. This presents a huge opportunity for the Muslim fashion industry, including the Nibras brand located in Sooko Mojokerto. This study aims to examine in depth the application of sharia marketing strategies through the 7Ps at Nibras House Sooko Mojokerto, as well as its implementation in digital marketing. The research method used a descriptive qualitative approach through interviews with the owner and employees of Nibras House Sooko Mojokerto. The results show that Nibras House Sooko Mojokerto has implemented sharia principles in all aspects of marketing with sharia-compliant products, fair prices, honest promotions, strategic locations, good staff, fast and responsive service processes, and good customer reviews. Additionally, Nibras House Sooko Mojokerto utilizes digital marketing through e-commerce and social media to expand its market and strengthen its competitiveness against new Muslim brands.